PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FESYEN INDONESIA MELALUI E-COMMERCE (Studi Kasus pada Konsumen di DKI Jakarta) - Andi Dwi Kurniawan (2022)
This research is a quantitative study that aims to determine the effect of product quality, price, and brand image on purchasing decisions for Indonesian fashion products through e-commerce. This research uses consumers in DKI Jakarta who have purchased Indonesian fashion products through e commerce as a sample. The sample used was 100 + 30 respondents, with the sampling technique using non-probability sampling, namely purposive sampling. Collecting data in this study used a questionnaire in the form of a google form which was distributed via social media. The hypothesis of this study to determine the effect of both partially and simultaneously from the independent and dependent variables. Tests in this study used descriptive analysis techniques, instruments, classical assumptions, multiple linear regression, and hypotheses with the SPSS version 29 analysis tool. And from the tests the results were obtained: (I) Product quality has a positive and significant effect on purchasing decisions (2) Price has a positive and significant effect on purchasing decisions, (3) brand image does not have a significant effect on purchasing decisions, (4) product quality, price, and brand image have a simultaneous effect on purchasing decisions.